Health disparities in youth and families research and applications - Carlo, Gustavo; Crockett, Lisa J.; Carranza, Miguel A. (Springer eBooks., 2011)
Amid its growing diversity and shifting demographics, the U.S. is still home to glaring health inequities by race, ethnicity, and class. Yet while it is customary to identify poverty as their root cause, other complex mechanisms are involved in their perpetuation. Based on recent major studies on African-American, Latino, Asian-American, and Native American populations, Health Disparities in Youth and Families offers a thorough, nuanced examination of a wide range of causal and protective factors. Rigorous theories and models take into account cultural, contextual, and personal variables, including the roles of family identity, school, and neighborhood, and motivation toward health awareness (with attention paid to less frequently studied phenomena such as within-group inequalities and the Hispanic Health Paradox). Contributors approach their subjects with realism as well as optimism as the book: Provides reliable information on the scope and etiology of health disparities. Identifies the methodological and political challenges associated with this issue. Proposes comprehensive, integrative models for understanding disparities. Features examples of innovative programs for improving minority health. Includes an in-depth chapter on substance use and mental health among Native American youth. Offers a useful starting point for the exchange of ideas necessary to address health disparities.